Fibropromotion: Fibrin-assisted soft-tissue promotion technique for root coverage using advanced platelet-rich fibrin - Sharanya Bose; Subhapriya Mandal; B. S. Ravi Prakash; Abhijit Chakraborty; Vivek Raghavji Devani (Wolters Kluwer Medknow Publications, 2020)
The periodontal plastic procedure aims to correct the soft-tissue deformities of the inadequate keratinized tissue or loss of attachment. The clinicians and researchers have tried various materials and techniques to maintain soft-tissue barrier. The literature supports the use of subepithelial connective tissue with satisfactory results. However, problems such as increased morbidity, safety concern, harvest quality, and insufficient procurement have impelled for better material. The third-generation autologous blood derivative: advanced platelet-rich fibrin (A-PRF) is an excellent alternative and fibropromotive material. The current case report discusses easy and reproducible fibrin-assisted soft-tissue promotion technique using A-PRF for root coverage of multiple defect.